The impact on colostrum oxidative stress, cytokines, and immune cells composition after SARS-CoV-2 infection during pregnancy - Graciliano, Nayara Gomes; Tenório, Micaely Cristinados Santos; Fragoso, Marilene Brandão Tenório; Moura, Fabiana Andréa; Botelho, Rayane Martins; Tanabe, Eloiza Lopes Lira; Borbely, Karen Steponavicius Cruz; Borbely, Alexandre Urban; Oliveira, Alane Cabral Menezes; Goulart, Marília Oliveira Fonseca (Frontiers in Immunology, 2022)
Background: Limited data are available regarding the differences between immunological, biochemical, and cellular contents of human colostrum following maternal infection during pregnancy with coronavirus 2 disease (COVID-19). Objective: To investigate whether maternal COVID-19 infection may affect immunological, biochemical, and cellular contents of human colostrum. Methods: Using a case-control study design, we collected colostrum from 14 lactating women with a previous diagnosis of COVID-19 during pregnancy and 12 without a clear diagnosis during September 2020 to May 2021. Colostrum samples were analysed for some enzymes and non-enzymatic oxidative stress markers (SOD, CAT, GPx, MDA, GSH, GSSG, H2O2, MPO) and for IL-1β, IL-6, tumour necrosis factor (TNF)-α, protein induced by interferon gamma (IP)-10, IL-8, IFN-λ1, IL12p70, IFN-α2, IFN-λ2/3, granulocyte macrophage colony stimulating factor (GM-CSF), IFN-β, IL-10 and IFN-γ, along with IgA and IgG for the SARS-CoV-2 S protein. We perform immunophenotyping to assess the frequency of different cell types in the colostrum. Results: Colostrum from the COVID-19 symptomatic group in pregnancy contained reduced levels of H2O2, IFN-ɑ2, and GM-CSF. This group had higher levels of GSH, and both NK cell subtypes CD3-CD56brightCD16-CD27+IFN-+ and CD3-CD56dimCD16+CD27- were also increased. Conclusion: The present results reinforce the protective role of colostrum even in the case of mild SARS-Cov-2 infection, in addition to demonstrating how adaptive the composition of colostrum is after infections. It also supports the recommendation to encourage lactating women to continue breastfeeding after COVID-19 illness.